2007
DOI: 10.1116/1.2768605
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of a field emission display prototype for indoor giant display application

Abstract: Architecture of field emission display based on a gate electrode of diabolo modeThe authors report the fabrication and characterization of a 4.5 in. field emission display ͑FED͒ prototype. The FED prototype consists of 14ϫ 14 matrix addressable pixels. The pixel is 5 mm in diameter. The characteristics including current-voltage properties, current stability, brightness, and image quality of the display prototype were characterized. The average static brightness of the display prototype is 2500 cd/ m 2 . Charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The size reduction and quantum confinement effect of 1D nanomaterials demonstrated considerably high current density and low turn-on voltage which provide a new opportunity in FE display with faster response, lower cost and lower power consumption. A number of studies have been reported to obtain a lower turn-on voltage and threshold fields using nanometre-size emitters [5][6][7][8]. These findings indicated that the FE performances were highly dependent on the materials with an adequate work function, higher aspect ratios and sharp edges.…”
Section: Introductionmentioning
confidence: 99%
“…The size reduction and quantum confinement effect of 1D nanomaterials demonstrated considerably high current density and low turn-on voltage which provide a new opportunity in FE display with faster response, lower cost and lower power consumption. A number of studies have been reported to obtain a lower turn-on voltage and threshold fields using nanometre-size emitters [5][6][7][8]. These findings indicated that the FE performances were highly dependent on the materials with an adequate work function, higher aspect ratios and sharp edges.…”
Section: Introductionmentioning
confidence: 99%